Quantitative Analysis of Epstein-Barr Virus Load by Using a Real-Time PCR Assay - Kimura, Hiroshi (American Society for Microbiology, 1999)
To measure the virus load in patients with symptomatic Epstein-Barr virus (EBV) infections, we used a real-time PCR assay to quantify the amount of EBV DNA in blood. The real-time PCR assay could detect from 2 to over 10(7) copies of EBV DNA with a wide linear range. We estimated the virus load in peripheral blood mononuclear cells (PBMNC) from patients with symptomatic EBV infections. The mean EBV-DNA copy number in the PBMNC was 10(3.7) copies/μg of DNA in patients with EBV-related lymphoproliferative disorders, 10(4.1) copies/μg of DNA in patients with chronic active EBV infections, and 10(2.2) copies/μg of DNA in patients with infectious mononucleosis. These numbers were significantly larger than those in either posttransplant patients or immunocompetent control patients without EBV-related diseases. In a patient with infectious mononucleosis, the virus load decreased as the symptoms resolved. The copy number of EBV DNA in PBMNC from symptomatic EBV infections was correlated with the EBV-positive cell number determined by the in situ hybridization assay (r = 0.842; P < 0.0001). These results indicate that the real-time PCR assay is useful for diagnosing symptomatic EBV infection and for monitoring the virus load.